PI Fuzzy Controller of Synchronous Boost Converter for Drug Storage Thermoelectric Cooler - Alvin Noer Ramadhan; Novie Ayub Windarko; Irianto Irianto (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
Medicines should be stored in a room at a suitable temperature because the condition of temperature affects the quality of the drug. Improper storage procedures may result in the drug being unable to cure effectively and cause drug damage which results in losses for pharmaceutical industry companies and patients. Therefore a controller for temperature is needed in the room so that it is constantly under the rules of room temperature for drug storage, which is 25 degrees Celsius. The following paperwork presents a simulation controller between PI controller and PI-Fuzzy logic controller in adjusting the voltage to match the set of points. The fuzzy logic controller automatically searches Kp value so the voltage output of the converter matches the desired set of points. The converter used is a synchronous boost converter as a voltage regulator and Peltier as a DC load which functions as a cooler. In this research, the system using PI controller was able to adjust the voltage to match the set point 60V with KP is 0.14089, Ki is 125.6738, and the settling time is 0.016 s. While the system using PI-Fuzzy logic controller, it was able to adjust the voltage to match the set point 60V with Kp is 0.08112, Ki is 125.6738, and settling time is 0.014 s. It can be concluded that the PI Fuzzy controller can find the KP value automatically and reach the desired set point. Keywords: peltier, PI cotroller, PI-fuuzzy logic controller, synchronous boost converter